Investigation of the price scale importance in the conditions of the post-soviet market society - Kerimov, Atik; Babayev, Azer (Technology audit and production reserves, 2017)
The object of research is modern ideas about the price scale and their inconsistency with the tasks of reforming the economic foundations of the post-Soviet society. One of the most problematic places of this object is the ideas that are ingrained at the level of the educational and scientific literature, either not having real grounds, or scholastic in nature. At the level of macroeconomic characteristics of the post-Soviet economy, this is shown in the fact that the classical idea of equal wages for equal work is not being realized. During the research, scientific methods of theoretical analysis, comparison and generalization, induction and deduction were used. Through these methods, the problem of the price scale from the highly specialized and strictly theoretical state is transferred into the plane of one of the fundamental categories of the economic structure of society. This issue has such tangible impact on the parameters of the social and economic life of modern society that each country shapes its understanding of the fundamentals of the national price scale. The post-war experience of the developed countries of Western Europe clearly shows that the post-Soviet republics have a clear positive example in this matter. Based on international experience and the provisions of international conventions, the post-Soviet republics need to derive the problem of the real price scale at the level of state policy in the field of income and wages. This can be another direction for the healthy integration of post-Soviet societies into the world space. The achieved qualitative result is determined by the following: the strengthening of the purchasing power of national money in the industrial countries actually went through the transformation of the price of labor into the economic basis of the price scale. Cooperation of the state and trade unions allows to bring under this process and the corresponding regulatory and legal basis. Thus, the functioning of the price scale ceases to be a spontaneous process.